Practical use of Seebeck and Pelter effects (Review) - Mikulionok, Ihor; Ivanenko, Olena (Vìsnik Nacìonalʹnogo tehnìčnogo unìversitetu Ukraïni <<Kiïvsʹkij polìtehnìčnij ìnstitut ìmenì Ìgorâ Sìkorsʹkogo>>. Serìâ <<Hìmìčna ìnženerìâ, ekologìâ ta resursozberežennâ>>, 2024)
The subject of research is industrial and household equipment and devices, the principle of operation of which is based on such thermoelectric phenomena as the Seebeck and Peltier effects. The purpose of the research is a critical analysis of the fields of practical application of the Peltier and Seebeck effects, as well as the constructive and technological design of the processes in which the specified effects are implemented to ensure a certain thermal regime, as well as the generation of electrical energy from waste heat. One of the main problems of today is global warming, environmental pollution and the increase in the cost of electricity. These problems can be partially solved with the help of thermoelectric phenomena, that is, physical phenomena caused by the relationship between electric current and heat flows in substances and contacts between them, which primarily include the Peltier and Seebeck effects. The indisputable advantages of thermoelectric means are their environmental safety, quiet operation and long service life. Seebeck and Peltier effects are used in chemical technology and related industries, renewable energy, construction, machine and instrument engineering, aerospace and military engineering, microelectronics, computer technology, medicine, personal hygiene devices, household appliances, and transportation. However, the low efficiency and the high cost of materials prevent the wide spread of thermoelectric technology. Wider application of thermoelectric technologies can be expected in case of development of new conductive materials with different energy levels of electrons in the conduction zone, as well as optimization of the geometry and structure of thermoelectric devices. Recently, intensive research has also been carried out on the so-called ionic Seebeck effect, which opens up new perspectives in thermoelectric phenomena, as well as the use of "magnetic thermoelectrics", or the spin Seebeck effect. This review can be useful to creators of new equipment and technology, because the fund of technical effects is widely used during the creation of innovative samples, which is an integral part of the information fund of inventors and helps them create simple, effective and bright solutions to technical problems.